2020
DOI: 10.1111/acel.13115
|View full text |Cite
|
Sign up to set email alerts
|

A lncRNA survey finds increases in neuroprotective LINC‐PINT in Parkinson’s disease substantia nigra

Abstract: Recent reports highlight regulatory functions of long noncoding RNAs (lncRNAs) in neurodegeneration and aging, but biomedical implications remain limited. Here, we report an rRNA‐depletion‐based long RNA‐Sequencing Resource of 65 substantia nigra, amygdala, and medial temporal gyrus samples from Parkinson's disease (PD) and matched control brains. Using a lncRNA‐focused analysis approach to identify functionally important transcripts, we discovered and prioritized many lncRNAs dysregulated in PD. Those include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(56 citation statements)
references
References 41 publications
0
54
0
Order By: Relevance
“…Disease age of onset in families with mutations in these genes is between 20 and 50, considerably earlier than 65 years of age, the typical onset age for the sporadic forms of the disease. Additionally, PD involves massive changes in RNA metabolism (La Cognata et al , ), both in brain neurons (Liu et al , ) and in patients’ leukocytes (Soreq et al , , , ; Simchovitz et al , ), but contributions of circular RNAs (circRNAs) to PD risks have so far remained unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Disease age of onset in families with mutations in these genes is between 20 and 50, considerably earlier than 65 years of age, the typical onset age for the sporadic forms of the disease. Additionally, PD involves massive changes in RNA metabolism (La Cognata et al , ), both in brain neurons (Liu et al , ) and in patients’ leukocytes (Soreq et al , , , ; Simchovitz et al , ), but contributions of circular RNAs (circRNAs) to PD risks have so far remained unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the inflammation regulator NFkB1 was only increased under SARS-CoV-2 infection ( Figure 2B ). Both DANCR and the sepsis-related neuroprotective lncRNA NEAT1, which initiates and maintains the membrane-less organelle of nuclear paraspeckles ( 30 , 33 , 39 ), were suppressed in SARS-CoV-2 infected cells ( Figure 2C ) (see corresponding Resource in Supplementary Table 1 for the full list of lncRNAs changed in NHBE and A549 cells infected with SARS-CoV-2, in NHBE cells infected with pandemic H1N1, and in lung inflammatory samples). Together, these observations indicated that inter-related changes in DANCR, NEAT1, and NFkB1 might play specific regulatory roles in the natural history of SARS-CoV-2 infection.…”
Section: Resultsmentioning
confidence: 99%
“…The lncRNA-mediated “overwatch” may avert cytokine storms characteristic of sepsis; and prevent detrimental life-threatening states which may develop where these and other mediators fail to harness overwhelming inflammation ( 35 ). Correspondingly, changes in inflammation-related ncRNAs, coupled with modified cholinergic surveillance, are evident in infectious, neuro-inflammatory and other conditions, including brain ramifications ( 30 , 37 , 119 , 128 130 ). These include, for instance, the activity of the brain’s miR-218 in conjunction with cholinergic machinery in the context of amyotrophic lateral sclerosis (ALS) ( 131 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, NEAT1 expression has been shown to be neuroprotective, since the interference-mediated depletion of NEAT1 aggravated death in the cells exposed to paraquat in a LRRK2-mediated manner. A study focused on identifying deregulated lncRNAs in the substantia nigra of PD patients described a pronounced increase in the Long Intergenic Non-Protein Coding RNA, p53-Induced Transcript, LINC-PINT, that was also observed in other models of PD and other neurodegenerative conditions [203]. Experimentally, the depletion of LINC-PINT exacerbated the death of cultured neuronal cells exposed to OS, suggesting a neuroprotective role of this transcript in diverse neurodegenerative disorders.…”
Section: Parkinson's Diseasementioning
confidence: 99%